Teknik Pembelajaran Matematika di Sekolah Luar Biasa Berbasis Kooperatif Tipe Think Pair Share - Mardliyati, Noor Fitri; Malasari, Putri Nur (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2023)
The learning capacity of students with special needs must be maximized in learning mathematics in SLB in an efficient and inclusive way. Think pair share, a cooperative learning strategy that promotes collaboration, active involvement, and contact between students, is one strategy that can be applied. In this study, we will examine how think-pair-share cooperative learning is used to teach mathematics in special schools and how it affects student learning outcomes. By using literature study methodology, this research method is qualitative. Reading and categorizing books and various scientific journal articles is a data collection method. The results of the study indicate that there is a beneficial effect of exposure to cooperative learning based on think pair share on student learning outcomes in special schools. Through collaboration in groups, students with special needs can support each other and gain a better understanding of mathematics. cooperative learning type think pair share also increases student participation in the learning process, develops individual thinking power, and increases their self-confidence. The application of cooperative learning-based mathematics learning techniques of the think pair share type requires the active role of the teacher as a facilitator and learning director. Teachers need to plan activities according to students' needs, provide appropriate support, and manage interactions between students. In order for the learning process to be successful, it is also crucial to pay attention to the qualities of study groups. This study significantly advances inclusive mathematics teaching strategies in special education settings. The results of this study are supposed to serve as a guide for math educators and teachers as they develop and implement engaging and effective math programs for students with special needs.